Effect of Neuromuscular Electrical Stimulation Addition in Exercise with Expiratory Muscle Trainer on FEV1 And FVC in Untrained Healthy Subjects - Langgeng Gunariadi; Imam Subadi; Dewi Poerwandari (Indian Journal of Forensic Medicine & Toxicology, 2021)
Coughing is a mechanism for expelling foreign particles or excess mucus in the airway by increasinghigh expiratory pressure. When coughing, the respiratory muscles that control cough production are theinspiratory and expiratory muscles. Weakness of the expiratory muscle can affect to the ability to generatesufficient pressure to cough. In generally, a decrease in respiratory muscle’s strength can occur in patientswho have experience of prolonged immobilization, elderly people who suffer from sarcopenia, to strokepatients. The untrained healthy persons were not realizing the effects of their lifestyle which can reduce therectus abdominis muscle as an additional expiratory muscle. If it occurred in long time, it will reduce thelung function capacity of force expiratory volume (FEV1) and force vital capacity (FVC). The subjects ofthis study were 16 untrained healthy males with aged 18-40 years. Furthermore, they divided into 2 groups,the intervention group with Expiratory Muscle Trainer (EMT) training plus of Neuromuscular ElectricalStimulation (NMES) on the rectus abdominis muscle and the control group with exercise with ExpiratoryMuscle Trainer only. The outcome was measured for FEV1 and FVC by spirometry. The results of this studywere indicating an increase in FEV1 and FVC in each group however. The intervention group was increaseof FEV1 0.22+0.22 (p value=0.18) and the control group was 0.01+0.39 (p value=0.92). The interventiongroup was increase of FVC 0.50+0.48 (p value=0.02) and the control group was 0.32+0.51 (p value=0.12).The FEV1 results between the two groups were not significant difference (p value=0.21) and as well as FVCresults after 4 weeks of training. In summary, this study concluded that EMT training with NMES increasedFVC even though the difference between the two was not significant.